FUZZY SUGENO UNTUK MENENTUKAN PENILAIAN KOMPETENSI KARYAWAN PT SCHNEIDER BATAM - simanjuntak, Pastima; Suharyanto, Cosmas Eko; Khairiyah, Riri (Journal Information System Development (ISD), 2018)
In a work process in companies, employees spearhead the first in the production process. Competencies possessed by each employee will show the quality of employees in performing their duties. It aims to look at the extent of competences of the employees, improvement and supervision competencies for employees. So that corporate leaders can make decisions choosing the best of the best employees. Assessment was conducted on the motive, knowledge, skills, and self-concept. So far there is no system that can be used to determine how big the competency of employees. therefore, this study used a system of decision-making using fuzzy logic withÂ  Sugeno method zero-orde for assessing the competence of employees in PT Schneider Batam. For the processing of data using MATLAB. The first step completion of competence assessment of employees using Sugeno that determines the input variables and output variables are set firmly, the second step is to convert the input variable into fuzzy sets with the process of fuzzification.